THE DOMINANT BIG FIVE PERSONALITY AMONG PRE-SERVICE TEACHERS IN THETEACHER EDUCATION INSTITUTES (IPGM) IN MALAYSIA - Ooi Soo Yuan; Rahimi Che Aman (Proceedings of The ICECRS, 2016)
The main purpose of this research is to identify the dominant Big Five Personality among pre service teachers in the Malaysian Teacher Education Institutes (IPGMs). The rationales of this study could be seen from three different aspects, which are the situational, literature and the Malaysian contexts. It is clear from current practice and the literatures that further research is needed to delve deeper into the understanding of personalities from the perspective of Big Five, especially among Malaysian pre service teachers. The data for this study was collected by survey using Neo FFI 3, which assessed the neuroticism, extraversion, openness to experience, agreeableness and conscientiousness of individuals. The samples consisted of 751 pre-services teachers selected through stratified and cluster sampling from the 27 IPGMs in Malaysia. Samples from the pre-service teacherscompleted the survey after their 12 weeks practicum in schools, as these 12 weeks practicum could be considered as the most stressful and crucial period of the pre service teachers training life in the IPGMs. Results revealed that majority of the pre-service teachers were conscientious. This interesting finding might have some positive indications to educations in Malaysia as it was in accordance with the MOE’s objectives.